Lmbrd1 expression is essential for the initiation of gastrulation. Issue 8 (8th April 2016) - Buers, Insa; Pennekamp, Petra; Nitschke, Yvonne; Lowe, Chrishanthi; Skryabin, Boris V.; Rutsch, Frank
Abstract: The rare inborn cblF defect of cobalamin metabolism is caused by mutations in the limb region 1 ( LMBR1 ) domain containing 1 gene ( LMBRD1 ). This defect is characterized by massive accumulation of free cobalamin in lysosomes and loss of mitochondrial succinyl‐CoA synthesis and cytosolic methionine synthesis. Affected children suffer from heart defects, developmental delay and megaloblastic anemia. LMBRD1 encodes for LMBD1, a predicted lysosomal cobalamin transport protein. In this study, we determine the physiological function of LMBRD1 during embryogenesis by generating Lmbrd1 deficient mice using the Cre/LoxP system. Complete loss of Lmbrd1 function is accompanied by early embryonic death in mice. Whole mount in situ hybridization studies against bone morphogenetic protein 4 and Nodal show that initial formation of the proximal–distal axis is unaffected in early embryonic stages whereas the initiation of gastrulation is disturbed shown by the expression pattern of even skipped homeotic gene 1 and fibroblast growth factor 8 in Lmbrd1 deficient mice. We conclude that intact function of LMBD1 is essential for the initiation of gastrulation.